Inverse Vulcanization of Norbornenylsilanes: Soluble Polymers with Controllable Molecular Properties via Siloxane Bonds. Issue 16 (23rd February 2022) - Scheiger, Johannes M.; Hoffmann, Maxi; Falkenstein, Patricia; Wang, Zhenwu; Rutschmann, Mark; Scheiger, Valentin W.; Grimm, Alexander; Urbschat, Klara; Sengpiel, Tobias; Matysik, Jörg; Wilhelm, Manfred; Levkin, Pavel A.; et al.
Abstract: The inverse vulcanization produces high sulfur content polymers from alkenes and elemental sulfur. Control over properties such as the molar mass or the solubility of polymers is not well established, and existing strategies lack predictability or require large variations of the composition. Systematic design principles are sought to allow for a targeted design of materials. Herein, we report on the inverse vulcanization of norbornenylsilanes (NBS), with a different number of hydrolysable groups at the silicon atom. Inverse vulcanization of mixtures of NBS followed by polycondensation yielded soluble high sulfur content copolymers (50 wt % S) with controllable weight average molar mass (MW ), polydispersity ( Đ ), glass transition temperature ( T G ), or zero‐shear viscosity ( η 0 ). Polycondensation was conducted in the melt with HCl as a catalyst, abolishing the need for a solvent. Purification by precipitation afforded polymers with a greatly reduced amount of low molar mass species. Abstract : Inverse vulcanized polymers of norbornenylsilanes with hydrolysable chloro‐ and ethoxy substituents were prepared and polycondensated to install defined amounts of M, D, or T siloxane bonds. The MW and T G of the soluble and branched polymers containing 50 wt % S could be varied systematically, whereas the elemental composition remained the same. Polymers with a sulfur content of 30 wt % could be prepared without low molar mass impurities.